Annotated Checklist of Aphodiinae (Coleoptera: Scarabaeidae) from Rio Grande do Sul and Santa Catarina, Brazil - Silva, Pedro Giovâni da (EntomoBrasilis, 2015)
An extensive literature review was performed to determine the list of Aphodiinae species reported in Rio Grande do Sul and Santa Catarina states. A total of 35 Aphodiinae species belonging to two tribes and 12 genera have been recorded in southern Brazil. Twenty-nine species (82.8%) were recorded in Santa Catarina and 16 (45.7%) in Rio Grande do Sul. Only nine species (25.7%) were reported to occur in both states. Ataenius Harold, 1867 was the genus with the greatest number of species (20), followed by Saprosites Redtenbacher, 1858 with only three species. Other genera were represented by one or two species. New lists should be made for other Brazilian states. Lista dos Aphodiinae (Coleoptera: Scarabaeidae) do Rio Grande do Sul e Santa Catarina, Brasil Resumo. Uma extensiva revisão da literatura foi realizada para listar as espécies de Aphodiinae dos estados de Santa Catarina e Rio Grande do Sul. Um total de 35 espécies de Aphodiinae pertencentes a duas tribos e 12 gêneros foi registrado para a região estudada. Vinte e nove espécies (82,8%) foram registradas para Santa Catarina e 16 (45,7%) para o Rio Grande do Sul. Apenas nove espécies (25,7%) foram compartilhadas por ambos os estados. Ataenius Harold, 1867 foi o gênero com o maior número de espécies (20), seguindo por Saprosites Redtenbacher, 1858 com apenas três espécies. Os outros gêneros foram representados por uma ou duas espécies. Novas listas devem ser feitas para outros estados brasileiros.